Optimization of doping design for planar P-N homologous junction perovskite solar cells - Liu, Wenfeng; Zhou, Ziyou; Zhou, Jicheng (Frontiers in Chemistry, 2024)
In this study, we used the solar cell capacitance simulator (SCAPS) to analyse numerically the performance of perovskite solar cells (PSCs) containing CH3NH3PbI3. The findings indicate that P-N homologous junction processing based on traditional P-I-N PSCs can enhance the photoelectric conversion efficiency (PCE). Furthermore, the authors analyzed the effect of uniform P-N doping of CH3NH3PbI3, concluding that the photoelectric efficiency can be improved from 16.10% to 19.03% after doping. In addition, the optical properties of PSCs under solar irradiation are simulated using finite difference time-domain (FDTD) software under AM1.5. This method is applied to investigate the effect of the P-N uniform junction on the internal electric field generated within the cell. The generation of this electric field promotes carrier separation and transmission, ultimately increasing the open circuit voltage (VOC) of the solar cell from 1.03 to 1.12 V. The usage of P-N junctions enhances PSCs performance and exhibits vast potential for designing and developing PSCs.